PELEMBAGAAN PARTAI POLITIK DI RUANG DIGITAL: STUDI TENTANG PKS, NASDEM, DAN PAN - Imam Syahid; Ilham Yuri Nanda; Denny Amansyah; Reyva Alviona Fernanda Priskilla; Melina Rosyida (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
ABSTRACT Political party institutionalization in Indonesia is often understood through formal indicators and quantitative scores, while the way institutionalization is displayed in organizational practice and digital public space has received far less attention. This article addresses that issue by using the 2024 BRIN Political Party Institutionalization Index (IPPP) as an entry point to examine how parties with high institutionalization scores present their identity, structure, and organizational continuity. The study employs a qualitative-interpretive approach based on secondary data drawn from party statutes and bylaws, official websites, and official social media accounts of the three parties with the highest IPPP scores: the Prosperous Justice Party (PKS), the National Democratic Party (NasDem), and the National Mandate Party (PAN). The analysis uses Randall and Svåsand’s framework of party institutionalization, particularly the dimensions of systemness, value infusion, decisional autonomy, and reification. The findings show that all three parties demonstrate relatively strong institutionalization, but through different patterns. PKS tends to display a more coherent form of institutionalization linking values, organizational structure, and communication. NasDem shows a pattern more strongly grounded in organizational effectiveness, continuity of political narrative, and the centrality of leadership figures. PAN, by contrast, occupies a more moderate position by combining structural stability, leadership symbolism, and institutional openness. This study argues that high institutionalization scores do not necessarily indicate a uniform model of party institutionalization. Instead, digital space is better understood as an arena through which party institutionalization is represented, negotiated, and made visible, rather than merely as a channel for political communication. Keywords: Political Party Institutionalization, Digital Space, Party Social Media, Party Websites, IPPP ABSTRAK Pelembagaan partai politik di Indonesia umumnya lebih sering dipahami melalui ukuran formal dan skor kuantitatif, sementara bagaimana pelembagaan itu ditampilkan dalam praktik organisasi dan ruang publik digital masih relatif jarang dibaca secara lebih dekat. Artikel ini berangkat dari persoalan tersebut dengan menempatkan Indeks Pelembagaan Partai Politik (IPPP) BRIN 2024 sebagai titik masuk untuk memahami bagaimana partai-partai dengan skor pelembagaan tinggi menampilkan identitas, struktur, dan keberlanjutan kelembagaannya. Penelitian ini menggunakan pendekatan kualitatif-interpretatif dengan memanfaatkan data sekunder yang bersumber dari Anggaran Dasar dan Anggaran Rumah Tangga (AD/ART), website resmi, serta media sosial resmi tiga partai politik dengan skor IPPP tertinggi, yaitu Partai Keadilan Sejahtera (PKS), Partai Nasional Demokrat (NasDem), dan Partai Amanat Nasional (PAN). Analisis dilakukan dengan menggunakan kerangka pelembagaan partai dari Randall dan Svåsand, terutama pada dimensi systemness, value infusion, decisional autonomy, dan reification. Hasil penelitian menunjukkan bahwa ketiga partai tersebut sama-sama memperlihatkan upaya pelembagaan yang relatif kuat, tetapi melalui corak yang berbeda. PKS cenderung menampilkan pelembagaan yang lebih koheren antara nilai, struktur, dan komunikasi organisasi. NasDem lebih menonjolkan pelembagaan yang bertumpu pada efektivitas organisasi, kesinambungan narasi politik, dan sentralitas figur kepemimpinan. Sementara itu, PAN menunjukkan pola yang lebih moderat dengan memadukan stabilitas struktural, simbol kepemimpinan, dan keterbukaan kelembagaan. Artikel ini menunjukkan bahwa skor pelembagaan yang tinggi tidak selalu menunjuk pada model pelembagaan yang seragam, dan bahwa ruang digital lebih tepat dibaca sebagai arena representasi pelembagaan partai daripada sekadar saluran komunikasi politik. Kata kunci: Pelembagaan Partai Politik, Ruang Digital, Media Sosial Partai, Website Partai, IPPP